2019
DOI: 10.3390/jcm8101590
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Alarmins in Serum and Exhaled Breath in Patients with Idiopathic Pulmonary Fibrosis: A Prospective One-Year Follow-Up Cohort Study

Abstract: Background: Recently, epithelial alarmins have been shown to play important roles in non-allergen driven respiratory diseases like idiopathic pulmonary fibrosis (IPF). Little is known about the expression of the epithelial alarmins in IPF. Methods: This study aimed to prospectively examine interleukin (IL)-25, IL-33, and thymic stromal lymphopoietin (TSLP) levels in the serum and exhaled breath condensate (EBC) in patients with IPF before and after one-year of antifibrotic treatment. A total of 82 volunteers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(90 reference statements)
2
7
0
Order By: Relevance
“…A six-month treatment with pirfenidone did not significantly change the EBC concentrations of IL-6, IL-8 and VEGF. This is consistent with earlier findings on other EBC cytokines [20]. There are, however, reports on antifibrotic treatment-induced changes in the cytokine profile in serum [37,38], but these did not include the cytokines investigated in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A six-month treatment with pirfenidone did not significantly change the EBC concentrations of IL-6, IL-8 and VEGF. This is consistent with earlier findings on other EBC cytokines [20]. There are, however, reports on antifibrotic treatment-induced changes in the cytokine profile in serum [37,38], but these did not include the cytokines investigated in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In their analysis of alarmins in serum and EBC, Majewski et al reported a weak but negative correlation between serum and EBC IL-33. Despite higher serum and EBC TSLP levels in IPF patients when compared to controls in that study, the concentrations of TSLP in these two materials did not correlate [20]. Krauss et al also did not find relationships between EBC and BALF concentrations of PGE2 and 8-isoprostane in patients with different interstitial lung diseases, including IPF [25].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, the contribution of DAMPs and the effect of targeting this therapeutically in fibrosis is less well explored. Majewski and colleagues examined the levels of IL-25, IL-33 and thymic stromal lymphopoietin (TSLP) in patients with IPF and followed them after one year of treatment with the antifibrotic drugs nintedanib or pirfenidone [ 252 ]. The baseline levels of TSLP were elevated in IPF patients compared with controls, while IL-25 and IL-33 levels did not vary.…”
Section: Targeting Senescence As a Potential Therapeutic Approach Formentioning
confidence: 99%